Computation and the Sociological Imagination. (November 2019) - Evans, James; Foster, Jacob G.
Computational sociology leverages new tools and data sources to expand the scope and scale of sociological inquiry. It's opening up an exciting frontier for sociologists of every stripe—from theorists and ethnographers to experimentalists and survey researchers. It expands the sociological imagination.